Exploring Challenges Faced by Nurses on Provision of Hormonal Contraceptives to Women on Antiretroviral Therapy in Selected Healthcare Facilities in Lilongwe District, Malawi - Mkwinda E; Thombozi E; Botha J; Chilinda I; Mandala E; Chipeta M (Dove Medical Press, 2022)
Esmie Mkwinda,1 Enalla Thombozi,2 Janet Botha,2 Idesi Chilinda,2 Edna Mandala,2 Mep Chipeta3 1Nursing Department, Saint John of God College of Health Sciences, Mzuzu, Malawi; 2Community and Mental Health Department, Kamuzu University of Health Sciences, Lilongwe, Malawi; 3Department of Nursing and Midwifery, Mzuzu University, Mzuzu, MalawiCorrespondence: Esmie Mkwinda, Saint John of God College of Health Sciences, P. O. Box 744, Mzuzu, Malawi, Tel +265999672324, Email esmeym@gmail.comBackground: Malawi is a low-income country with a high maternal mortality rate, unmet need for family planning and high reports (41%) of unintended pregnancies. Women on Antiretroviral Therapy (ART) continued to experience unintended pregnancies after using hormonal contraceptives provided by nurses in the family planning clinics. However, the unintended pregnancies could affect the sexual and reproductive health of women and decisions of nurses on contraceptive provision to women on ART.Objective: The purpose of the study was to explore challenges faced by nurses in the provision of hormonal contraceptives to women on ART in selected clinics in Lilongwe, Malawi.Methods: A qualitative approach using an explorative design was used in this study. Eight (8) participants were selected purposefully from five public family planning clinics in Lilongwe. They were interviewed individually using a semi-structured interview guide. Data were analyzed using a content analysis guide.Results: Three themes emerged from the data and these were as follows: limited knowledge of nurses; inadequate resources and inadequate support. Results revealed that nurses had limited knowledge of contraceptives to provide to women on ART due to lack of ART content in the contraceptive training which they had. They also lacked clinical and human resources and adequate time to teach clients which affected provision of the right hormonal contraceptives to women on ART. Furthermore, they needed support in the form of supervision, reference materials and integration of ART and contraceptive provision services.Conclusion: The challenges that nurses faced had an influence on the provision of contraceptives to women on ART. The study recommends that nurses should be trained on the provision of contraceptives to women on ART and be provided with the required resources and support for proper care to be achieved. Furthermore, there is a need for clear guidelines on hormonal contraceptives that women on ART could get and the integration of ART and family planning services.Keywords: antiretroviral therapy, hormonal contraceptives, unintended pregnancies, nurses, challenges